A Method of Solubilizing and Concentrating Astaxanthin and Other Carotenoids - Kiyotaka Y. Hara; Shuwa Yagi; Yoko Hirono-Hara; Hiroshi Kikukawa (Marine Drugs, 2021)
The valuable marine carotenoid, astaxanthin, is used in supplements, medicines and cosmetics. In this study, crustacyanin, an astaxanthin-binding protein, was used to solubilize and concentrate astaxanthin. The recombinant crustacyanin of European lobster spontaneously formed an inclusion body when it was over-expressed in Escherichia coli. In this study, fusing the NusA-tag to the crustacyanin subunits made it possible to express in a soluble fraction and solubilize astaxanthin in aqueous solution. By cutting off the NusA-tag, the crustacyanin subunits generated the pure insoluble form, and captured and concentrated astaxanthin. Overall, the attaching and releasing NusA-tag method has the potential to supply solubilized carotenoids in aqueous solution and concentrated carotenoids, respectively.